2013
DOI: 10.1590/0004-282x20130104
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of motor function and decreased need for postnatal shunting in children who had undergone intrauterine myelomeningocele repair

Abstract: Objective To compare neuromotor development between patients who did and those who did not undergo intrauterine myelomeningocele repair. Methods Children with myelomeningocele aged between 3.5 and 6 years who did undergo intrauterine repair (Group A, n=6) or not (Group B; n=7) were assessed for neuromotor development at both anatomical and functional levels, need for orthoses, and cognitive function. Results Intrauterine myelomeningocele repair significantly improved motor function. The functional level wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…1 Smaller clinical studies in other centers have had similar results. [19][20][21] Our findings are in keeping with these studies because we found that 81% of fetuses that underwent prenatal repair had resolved cerebellar ectopia postnatally, a result that was not observed in any of the fetuses that underwent postnatal repair. Our study adds to the clinical literature by describing in more detail the imaging findings on both pre-and postnatal MR imaging by adapting the grading system used by Sutton et al 2 on fetal MR imaging, which can be applied to clinical practice.…”
Section: Discussionsupporting
confidence: 86%
“…1 Smaller clinical studies in other centers have had similar results. [19][20][21] Our findings are in keeping with these studies because we found that 81% of fetuses that underwent prenatal repair had resolved cerebellar ectopia postnatally, a result that was not observed in any of the fetuses that underwent postnatal repair. Our study adds to the clinical literature by describing in more detail the imaging findings on both pre-and postnatal MR imaging by adapting the grading system used by Sutton et al 2 on fetal MR imaging, which can be applied to clinical practice.…”
Section: Discussionsupporting
confidence: 86%
“…Finally, we reviewed all retrospective cohort studies and case series reporting on neurodevelopmental outcome of infants after prenatal repair of SBA (Table S1). These could not be included in the qualitative and quantitative analysis since they did not match the inclusion criteria regarding the study design, and only one of these reported on a postnatal‐repair cohort as a control group. After including this study in the meta‐analysis, the conclusions regarding the primary outcome measure and selected secondary outcome measures (shunt placement rate, independent ambulation) did not change (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Appendix S1 Search strategy Figure S1 Meta-analysis for presence of neurodevelopmental impairment (a), need for ventriculoperitoneal shunt placement by 12 months postpartum (b) and independent ambulation at 30 months (c), in infants that had prenatal vs those that had postnatal surgical repair of spina bifida aperta, including findings of study by Faria et al 25 .…”
Section: Supporting Information On the Internetmentioning
confidence: 99%
“…This closure disorder occurs in the third week of gestation, and biochemical, genetic, and environmental phenomena are involved in its genesis. Ninety percent of myelomeningocele patients develop hydrocephalus due to Chiari malformation type II and require ventricular shunts after birth [26]. Therefore, the main goal of the fetal surgery for myelomeningocele before 27 weeks of gestation is to reduce the ventricular shunt rates and revert the Chiari type II.…”
Section: Myelomeningocelementioning
confidence: 99%